Protein kinase D1 conditional null mice show minimal bone loss following ovariectomy. (15th October 2018) - Bollag, Wendy B.; Ding, Ke-Hong; Choudhary, Vivek; Xu, Jianrui; Zhong, Qing; Elsayed, Ranya; Bailey, Lakiea J.; Elsalanty, Mohammed; Yu, Kanglun; Johnson, Maribeth H.; McGee-Lawrence, Meghan E.; Isales, Carlos M.
Abstract: We previously found that 3- and 6-month-old male mice with conditional ablation of protein kinase D1 (PRKD1) in osteoprogenitor cells (expressing Osterix) exhibited reduced bone mass. Others have demonstrated similar effects in young female PRKD1-deficient mice. Here we examined the bone resorptive response of adult female floxed control and conditional knockout (cKO) mice undergoing sham surgery or ovariectomy (OVX). Femoral and tibial bone mineral density (BMD) values were significantly reduced upon OVX in control, but not cKO, females compared to the respective sham-operated mice. Micro-CT analysis showed that OVX significantly increased trabecular number and decreased trabecular spacing in cKO but not control mice. Finally, in control mice serum levels of a marker of bone resorption (pyridinoline crosslinks) and the osteoclast activator RANKL significantly increased upon OVX; however, no such OVX-induced increase was observed in cKO mice. Our results suggest the potential importance of PRKD1 in response to estrogen loss in bone. Highlights: Floxed control and protein kinase D1 conditional knockout (cKO) mice were examined. Ovariectomy (OVX) decreased bone mineral density in control but not cKO mice. OVX elevated serum levels of a bone resorption marker in control but not cKO mice. OVX increased serum levels of an osteoclast activator in control but not cKO mice. Protein kinase D1 likely plays a role in bone responses to estrogen and its loss.